The Structural and Cost Analysis of Musholla Baitul Munjiy, Semarang Regency - Dyah Kumala, Nevy Risna; Mahfuda, Anno (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
Prayer rooms and mosques have evolved significantly, influenced by their respective regions' cultural and architectural traditions. Mosque construction presents challenges in balancing structural safety, long-term durability, and cost efficiency. This study uniquely combines advanced structural simulation with comprehensive cost analysis to provide an innovative design approach for mosques in earthquake-prone regions. This study utilizes SAP2000 to demonstrate how structural simulations can optimize traditional mosque designs for improved seismic resilience and cost efficiency, using the Musholla Baitul Munjiy in Bawen, Semarang, as a case study. The analysis revealed that some beams and columns had insufficient load-bearing capacity, especially concerning deflection limits. Minor modifications to beam and column dimensions significantly enhanced structural stability, highlighting the potential of targeted design improvements in seismic areas. The refined design met safety standards under seismic simulations and validated the proposed modifications' effectiveness. The findings offer a replicable design framework to enhance both structural resilience and economic viability of small-scale religious buildings in seismic-prone regions.